Linear scattering theory of short-pulse reflectometry. (1st January 2023) - Krutkin, O; Brunner, S; Coda, S; Aleynikov, P
Abstract: The linear scattering theory of short pulse reflectometry is presented. An expression for the scattering signal is obtained by applying the perturbation theory approach for solving the Helmholtz equation. Based on these analytical results, a method for measuring the radial wavenumber spectrum of the turbulence is suggested. Analytical results are validated against full-wave numerical modelling.